Nymph and egg of Melanemerella brasiliana (Ephemeroptera: Ephemerelloidea: Melanemerellidae), with comments on its systematic position and the higher classification of Ephemerelloidea - Molineri, Carlos (2003)
The genus Melanemerella has been of uncertain familial placement since its description in 1920. It was first assigned to the family Ephemerellidae, later transferred to Tricorythidae, and finally to Leptophlebiidae. The uncertain familial placement was partly a result of its unique characters and inadequate description based on a single female imago. We describe for the first time eggs and nymphs of both sexes. As a result of a cladistic analysis done to elucidate the correct family assignment of Melanemerella, we demonstrate that the genus is not a Leptohyphidae, Coryphoridae, or Tricorythidae. Melanemerella appears to be related to Teloganella (Teloganellidae) and Manohyphella (Teloganodidae), although the relationship is poorly supported. We propose the establishment of the family Melanemerellidae (new status) for this monobasic genus.